From blossoms to biofuel: a novel approach to bioethanol production - Bhattacharyya, Shalini; Manian, Ramesh Pathy (Discover applied sciences, 2025)
Floral wastes comprise a significant portion of agro-wastes generated, globally, this waste originates from various ornamental, ceremonial, and religious practices. It poses a great threat to the environment – as most of it is dumped in landfills and nearby water bodies, causing greenhouse gas emissions and pollution. The wasted flowers not only represent an overlooked reserve of highly fermentable sugar content, but also can bridge the gap between the global efforts of sustainable energy production and waste reduction. Floral wastes have currently emerged to be a promising source of renewable fuel, and recent advances in anaerobic fermentation techniques are providing a boost to such unconventional feedstock alternatives. This review analyses trends observed in the production of biofuel from floral biomass—a niche yet highly critical source of lignocellulosic compounds that can be capitalized if tapped efficiently. Here, we quantify the contribution of floral residues within the total generated agro‐waste, and analyse their organic composition, while evaluating their respective energy yields compared to traditional substrates. In this article, we present an overview of the current literature on the complete process chain from pre-treatment, enzymatic hydrolysis, fermentation, and distillation, focusing on established protocols and novel approaches that mitigate the principal issues such as high moisture content, seasonal variability, and the occurrence of inhibitory compounds. According to comparative studies of some flower species (such as marigold, hibiscus and rose), they have higher conversion efficiency due to better sugar content, while others may have poorer yields. They are also seeking to advance, not to mention technology, to facilitate efficiency, and reduce costs. Highlights Waste flowers recognized as a novel, underutilized lignocellulosic feedstock for bioethanol production. Flowers like rose, hibiscus, mahua, jasmine and marigold offer high reducing sugar yields with low levels of lignin. Floral waste valorization supports circular economy by converting ceremonial waste into valuable products, like fuel. Advanced methods like strain modification and enzyme optimization enhance ethanol yield from floral biomass. Seasonal variability and presence of inhibitors pose challenges for consistent floral feedstock supply. LCA studies confirm floral bioethanol reduces GHG emissions and environmental burden.